2016
DOI: 10.1002/ijc.30450
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine sonic hedgehog signaling contributes significantly to acquired steroidogenesis in the prostate tumor microenvironment

Abstract: Despite the substantial benefit of androgen deprivation therapy (ADT) for metastatic prostate cancer, patients often progress to castration-resistant disease (CRPC) that is more difficult to treat. CRPC is associated with renewed androgen receptor activity in tumor cells and restoration of tumor androgen levels through acquired intratumoral steroidogenesis (AIS). Although prostate cancer (PCa) cells have been shown to have steroidogenic capability in vitro, we previously found that benign prostate stromal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Notably, the relevance of increased concentration of androgens in cells with ZEB1 knockdown may be associated with activation of AR during EMT (6). Therefore, an increase in the expression of steroidogenic enzymes has been suggested as a mechanism underlying resistance to ADT (22,23). According to the present results, it may be hypothesized that an increase in androgen synthesis could lead to an increase in the activation of AR due to its increased availability.…”
Section: Discussionmentioning
confidence: 52%
“…Notably, the relevance of increased concentration of androgens in cells with ZEB1 knockdown may be associated with activation of AR during EMT (6). Therefore, an increase in the expression of steroidogenic enzymes has been suggested as a mechanism underlying resistance to ADT (22,23). According to the present results, it may be hypothesized that an increase in androgen synthesis could lead to an increase in the activation of AR due to its increased availability.…”
Section: Discussionmentioning
confidence: 52%
“…Of note, it has also been suggested that paracrine type Shh signaling is involved in the local steroidogenesis in PCa [47]. Although it is generally believed that local steroidogenesis occurs within the tumor, there have been several reports stating that the stroma is also capable of steroidogenesis [47,48,115].…”
Section: Modulation Of Hedgehog Signaling By Androgen the Male Hormonementioning
confidence: 99%
“…Hh signaling regulates cell fate determination, proliferation, and differentiation (King et al, 2008). Moreover, over-activation of Hh signaling is associated with the tumorigenesis (Hirotsu et al, 2010;Galimberti et al, 2012;Lubik et al, 2017;Rennert et al, 2017). In mammals, the Hh pathway consists of three Hh ligands, indian (IHH), desert (DHH), and sonic (SHH); the membrane receptor patched (PTCH) 1 and 2; and the transmembrane signal transducer protein smoothened (SMO) (Wijgerde et al, 2005).…”
Section: Introductionmentioning
confidence: 99%